Copper-catalyzed chemoselective oxidative o-aroylation of 2-acetylphenols, alkyl salicylates and 1, 3-dicarbonyl compounds using styrene derivatives. (26th March 2021) - Kumar, Upendra; Sharma, Ajay; Kumar, Naveen; Pandey, Satyendra Kumar
Abstract: A novel copper-catalyzed chemoselective oxidative O -aroylation of 2-acetylphenols, alkyl salicylates and 1, 3-dicarbonyl compounds with a wide range of styrene derivatives are described. This approach provides an efficient chemoselective preparation of phenol, alkyl salicylate and enol esters in good to excellent yields. This method represents an alternative protocol for the classical esterification reactions. Graphical abstract: Image 1 Highlights: Copper-catalyzed directing group assisted aroylation of phenols. Chemoselective approach. TBHP used as oxidant. Additive, base, and ligand free, proceeds under mild conditions. An alternative approach for the classical esterification reactions.